2017
DOI: 10.1371/journal.pone.0188630
|View full text |Cite
|
Sign up to set email alerts
|

Vertical organization of the division of labor within nests of the Florida harvester ant, Pogonomyrmex badius

Abstract: In the Florida harvester ant, Pogonomyrmex badius, foragers occur only in the top 15 cm of the nest, whereas brood and brood-care workers reside mostly in the deepest regions, yet the food and seeds foragers collect must be transported downward 30 to 80 cm to seed chambers and up to 2 m to brood chambers. Using mark-recapture techniques with fluorescent printer's ink, we identified a class of workers that ranges widely within the vertical structure of the nest, rapidly moving materials dropped by foragers in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Even though less than half of internodes contained carton galleries, we found that the majority of workers and most of the brood resided in internodes with carton, suggesting they serve as brood storage. The shape of vertical Azteca worker distributions resembled the distribution patterns of several ground-nesting ant species 21,62 , which may reflect comparable resource proximity or available nest volume.…”
Section: Discussionmentioning
confidence: 67%
“…Even though less than half of internodes contained carton galleries, we found that the majority of workers and most of the brood resided in internodes with carton, suggesting they serve as brood storage. The shape of vertical Azteca worker distributions resembled the distribution patterns of several ground-nesting ant species 21,62 , which may reflect comparable resource proximity or available nest volume.…”
Section: Discussionmentioning
confidence: 67%
“…Based on data, we can speculate that there are typical “queen galls” that are occupied by the queen and her incipient colony from the beginning, then by brood and young workers as they are produced. Later, most of the worker population migrates to other galls, thereby deeply modifying their architecture as they grow in age and number, as happens in some ground-dwelling ants [66,67].…”
Section: Discussionmentioning
confidence: 99%
“…Workers have task-specific CHC profiles because task performance, e.g., nest building, brood tending, or foraging outside the nest influence the CHC profiles (Wagner et al, 1998 ; Kaib et al, 2000 ). Furthermore, the mixing of CHCs between individuals of a colony is not complete because workers within a task-group encounter and interact with each other more frequently than between task-groups (Sendova-Franks and Franks, 1995 ; Mersch et al, 2013 ; Pamminger et al, 2014 ; Tschinkel and Hanley, 2017 ). Based on these systematic differences in CHC profiles, workers are able to discriminate between nestmates performing different tasks (Bonavita-Cougourdan et al, 1993 ; Greene and Gordon, 2003 ).…”
Section: Introductionmentioning
confidence: 99%